The Effect of Electronic Educational Games on the Information Generation Skills of the First Intermediate Grade Students in Mathematics - Yusur Imad Salman; Dr. Lina Fouad Jawad (Migration Letters, 2023)
The research aimed to identify the effect of electronic educational games on the achievement and information generation skills of first-grade Intermediate school female students in the schools of the General Directorate of Education in Baghdad/Al-Karkh III. To achieve this goal, the following two zero hypotheses were formulated: “There is no statistically significant difference at the significance level (0.05) between the average scores of the female students of the experimental group who studied using electronic educational games, and the scores of the female students of the control group who studied using the usual method in the mathematics achievement test.” “There is no statistically significant difference at the level of significance (0.05) between the average scores of the female students of the experimental group who studied using electronic educational games, and the scores of the female students of the control group who studied using the usual method in the test of information generation skills in mathematics.” The research population was determined as it represented all female students in the first intermediate grade in the Intermediate and secondary day schools affiliated with the General Directorate of Education of Baghdad/Al-Karkh III for the academic year (2022-2023). The Hashimiya Intermediate School for Girls was chosen intentionally, and the research sample consisted of (60) students, with (30) female students. in the experimental group, and (30) students for the control group. For the purpose of collecting data for the research, an achievement test and an information generation skills test were prepared. The achievement test consisted of (32) objective multiple-choice items, and the information generation skills test in its final form consisted of (16) essay items. Appropriate statistical analyzes were conducted, where the difficulty, ease, and discrimination coefficients were calculated for all items of the two tests. The validity of the two tests was verified, their stability was calculated, and they were found acceptable. The effectiveness of the false alternatives to the achievement test was good, and the correlation coefficients were calculated to test information generation skills, and after statistical tools were chosen to analyze the results. Applying the test such as the Statistical Portfolio for the Social Sciences (SPSS-22), Levene’s test for two independent samples, and using the t-test for two independent samples. The results indicated: 1-The female students of the experimental group who studied using electronic educational games outperformed the female students of the control group who studied using the usual method in the achievement test. 2- The female students of the experimental group who studied using electronic educational games outperformed the female students of the control group who studied using the usual method in the test of information generation skills in mathematics.